Academic self-efficacy in first year students college of health sciences - López Walle, Jeanette M.; Rangel, Yunuen Socorro; Blanco Vega, Humberto; Blanco Ornelas, José René; González Hernández, Martín Alonso; Mendoza, Gerónimo (2014)
Self-efficacy learning is an important component of learning for college. Academic self-efficacy refers to the degree of confidence that health sciences students could successfully complete on college-task. The purpose of this research lies on the specific characteristics of health sciences students according to their academic self-efficacy by comparing their profiles with students that chose a different discipline. The Academic self-efficacy sample was done to 2089 subjects: 902 women and 1187 men, all of them freshmen students from the different careers at the Autonomous University of Chihuahua who responded to a survey questionnaire, with an average age of 18.23 years (SD = 0.74). This is a quantitative approach with a descriptive survey design type. The results obtained by comparing students of health sciences, with students from other disciplines show that perceived self-efficacy in academic behaviors is very similar each other.